PRE-TREATMENT OF BITUMINIZED NPP WASTES FOR DISPOSAL IN NEAR-SURFACE REPOSITORY (Brazilian Journal of Radiation Sciences, 2019)
The implementation of the national repository is an important technical requirement, and a legal requirement for the entry into operation of the nuclear power plant Angra 3. The Brazilian repository is being planned to be a near-surface one. In Brazil the low and intermediate level radioactive wastes are immobilized using cement and bitumen for Angra 1 and Angra 2 NPP, respectively. The main problems due to the disposal of bituminized wastes in repositories are swelling of the waste products and their degradation in the long term. To accommodate the swelling of the bituminized wastes, the drums are filled up to 70 - 90% of their volume, which reduces the structural the repository stability and the disposal availability. Countries, which use bitumen in the solidification of NPP´s radioactive waste and have near-surface repositories, need to immobilize this bituminized waste within other drums containing cement pastes or mortars to disposal them. This study aims to find solutions for the storage in surface repository of bituminized radioactive waste products, making them compatible with the acceptance criteria of cemented waste products. It was also performed a modeling with the results obtained in the leaching test using the ALT program and defined the transport model of the cesium leachate element and it was verified that in the early times the leaching was governed by the diffusion model and later by the partition model. The results obtained in this study can be used in the evaluation of performance of repositories.